Fiscal and monetary policy for difficult times: MMT solutions - Joëlle Leclaire (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
This article considers the current economic situation from the lens of modern money theory (MMT) and expresses a policy response rooted in post-Keynesian theory and empirical data for the US and the euro area. First, MMT supports targeted deficit spending to promote production. Increasing domestic supply will reduce the prices of goods and energy. Second, MMT advocates for reducing the interest rate to make production more profitable. Third, MMT pushes for a job guarantee and increased unionization to alleviate wage pressure. Fourth, MMT believes in rationing, postponed consumption, patriotic saving, and regulation. Increasing interest rates and limiting government deficit spending are not the only ways to address the post-COVID-19 period. We show there are better ways to restore price stability.
Keywords: E12; E42; E43; E44; E63; G18; H63; 330; modern money theory; monetary policy; fiscal policy; government debt; interest rate; inflation